2016
DOI: 10.1111/ijpo.12167
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and adiposity indicators associated with cardiovascular biomarkers in youth with type 1 diabetes followed prospectively

Abstract: Excess adiposity is associated with increased cardiovascular risk factors in this sample of youth with type 1 diabetes. Non-significant associations with adiponectin and 8-iso-PGF2α suggest potential differences from the general population in the role of adiposity in cardiovascular health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 27 publications
2
18
0
1
Order By: Relevance
“…This fat distribution has been related to glucose control in teenagers, and the excess of adipose tissue has been linked to cardiovascular risk factors in T1D. 28) Our study showed similar inflammatory cytokine levels in diabetic patients compared to controls, which is in agreement with the literature since most T1D patients considered in this study had adequate metabolic control (glycosylated hemoglobin<7.5%) and were diagnosed less than 1 year prior. Recently, Alnek et al, 29) in concordance with our study, found elevated level of IL-1β but not IL-6 or TNF-α in T1D children.…”
Section: Correlation Analysis Between Inflammatory Cytokines Level supporting
confidence: 92%
“…This fat distribution has been related to glucose control in teenagers, and the excess of adipose tissue has been linked to cardiovascular risk factors in T1D. 28) Our study showed similar inflammatory cytokine levels in diabetic patients compared to controls, which is in agreement with the literature since most T1D patients considered in this study had adequate metabolic control (glycosylated hemoglobin<7.5%) and were diagnosed less than 1 year prior. Recently, Alnek et al, 29) in concordance with our study, found elevated level of IL-1β but not IL-6 or TNF-α in T1D children.…”
Section: Correlation Analysis Between Inflammatory Cytokines Level supporting
confidence: 92%
“…To the best of our knowledge, this is the first study to indicate an inverse relationship between adiposity and bone density in youth with type 1 diabetes, who lack endogenous insulin production. Previous evidence in this sample of youth with type 1 diabetes indicates that adiposity is positively associated with CRP (19). However, the relationship of adiposity with total body BMD remained significant after adjusting for CRP.…”
Section: Discussionmentioning
confidence: 62%
“…However, this physiologic mechanism may be uncoupled in type 1 diabetes due to the destruction of pancreatic β-cells. Further, the association of increased adiposity with increased inflammation (18, 19) may lead to lower BMD. Previous studies investigating BMD predictors in type 1 diabetes have relied on BMI as an indicator of adiposity (20, 21).…”
Section: Introductionmentioning
confidence: 99%
“…29 However, Bascarin et al showed an unchanged high obesity frequency between 1999 and 2009 in an American population of children/adolescents with T1D 31 and another study with a 18-year follow-up period found a huge increase in the rate of obesity in patients with T1D. 4 This prevalence of obesity in T1D patients is worrying as obesity may have physical 8,9,32 as well as psychological implications. 12 We have no obvious explanations why the Danish T1D population had the lowest median BMISDS in the Nordic countries, but the differences in BMISDS between Denmark, Sweden, and Norway were relatively small (<0.13 SDS).…”
Section: Bmisds Adj Vs Insulin Dose and Injection Modalitymentioning
confidence: 99%